Clinical Utility of CA125 Levels in Predicting Laparoscopically Confirmed Salpingitis in Patients With Clinically Diagnosed Pelvic Inflammatory Disease. Issue 4 (1998) - Moore, E.; Soper, D. E.
Abstract : Objective: The purpose of this study was to determine the utility of serum CA125 determinations in diagnosing acute salpingitis. Methods: CA125 levels were determined for 34 women with the clinical diagnosis of pelvic inflammatory disease (PID). Acute salpingitis was confirmed laparoscopically in 28 women (82.3%). Results: Twenty patients (71.4%) with laparoscopically confirmed acute salpingitis had CA125 levels greater than 7.5 units, compared with no patients (0/6) with laparoscopically normal tubes ( P = 0.002). The degree of elevation of CA125 levels correlated with the severity of tubal inflammation noted at laparoscopy. All patients with levels above 16 units had laparoscopically severe salpingitis. Conclusions: We conclude that while CA125 levels above 7.5 units may modestly improve the ability of the clinical diagnosis of PID to accurately reflect visually confirmed acute salpingitis, limitations of the test make its clinical utility questionable.